An investigation into fracture behavior of geopolymer concrete with digital image correlation technique. (30th November 2017) - Xie, Z.L.; Zhou, H.F.; Lu, L.J.; Chen, Z.A.
Highlights: DIC was proposed to monitor the crack tip field of fly ash based GPC. CTOD and crack extension length were achieved with the help of DIC. Crack growth behavior of fly ash based GPC was elaborated. Crack propagation can be evidently manifested in COD and crack extension length. Abstract: Fly ash based geopolymer concrete (GPC) is gaining significant interest as a greener alternative to ordinary Portland cement concrete over the past decades. Its fracture behavior, especially the crack growth behavior, has received few attentions, possibly hindered by the difficulties in the monitoring of crack tip field with conventional measurement technique. Recently, digital image correction (DIC) has opened up the opportunity to gain a deep insight into its fracture behavior. Therefore, an investigation into the fracture behavior of fly ash based GPC with the use of DIC was performed. First, three-point bending tests on notched beam specimens were conducted. The displacement field of beam specimen was measured by DIC. Then, crack opening displacement (COD), crack extension length and mid-span deflection were achieved and the crack growth in fly ash based GPC were elaborated. Finally, the fracture energy and fracture toughness were calculated. The results show that DIC can be a useful technique for the monitoring of crack tip field. The crack propagation in fly ash based GPC can be evidently manifested in COD and crack extension length. The normalized crack extension length may be employed as a fracture criterion to pronounce the onset of unstable crack propagation in fly ash based GPC.